No evidence for the 'rate‐of‐living' theory across the tetrapod tree of life. Issue 5 (14th February 2020) - Stark, Gavin; Pincheira‐Donoso, Daniel; Meiri, Shai
Abstract: Aim: The 'rate‐of‐living' theory predicts that life expectancy is a negative function of the rates at which organisms metabolize. According to this theory, factors that accelerate metabolic rates, such as high body temperature and active foraging, lead to organismic 'wear‐out'. This process reduces life span through an accumulation of biochemical errors and the build‐up of toxic metabolic by‐products. Although the rate‐of‐living theory is a keystone underlying our understanding of life‐history trade‐offs, its validity has been recently questioned. The rate‐of‐living theory has never been tested on a global scale in a phylogenetic framework, or across both endotherms and ectotherms. Here, we test several of its fundamental predictions across the tetrapod tree of life. Location: Global. Time period: Present. Major taxa studied: Land vertebrates. Methods: Using a dataset spanning the life span data of 4, 100 land vertebrate species (2, 214 endotherms, 1, 886 ectotherms), we performed the most comprehensive test to date of the fundamental predictions underlying the rate‐of‐living theory. We investigated how metabolic rates, and a range of factors generally perceived to be strongly associated with them, relate to longevity. Results: Our findings did not support the predictions of the rate‐of‐living theory. Basal and field metabolic rates, seasonality, and activity times, as well as reptile body temperatures and foraging ecology, were found to be unrelated to longevity. In contrast, lower longevity across ectotherm species was associated with high environmental temperatures. Main conclusions: We conclude that the rate‐of‐living theory does not hold true for terrestrial vertebrates, and suggest that life expectancy is driven by selection arising from extrinsic mortality factors. A simple link between metabolic rates, oxidative damage and life span is not supported. Importantly, our findings highlight the potential for rapid warming, resulting from the current increase in global temperatures, to drive accelerated rates of senescence in ectotherms.